ANALYZING MAIN AND SUBORDINATE CLAUSES IN THE WEVERSE MAGAZINE - Ariffani, Amanda; Nopriyanti, Irnella; Wulandari, Shinta Desti (Universitas Ahmad Dahlan, 2021)
AbstractReading is activities that always do by EFL students; through reading, students can gain knowledge or get information from text like a printed textbook, E-book, magazine, article, news, and others. However, EFL students must understand what they read and the structural grammar of the text they already read. In grammar, there are term clauses that are divided into five parts: Main clause, Subordinate clause, Noun clause, Adjective clause, and Adverb clause. This article will focus on the main and subordinate clauses applied in the sentence on every Weverse magazine. Weverse itself is an online website that includes some hot news about K-pop idols under HYBE labels like BTS, TXT that a worldwide superstar boy group. This article uses descriptive qualitative research that aims to analyze the main and subordinate clauses in Weverse Magazine. This study will show how the main and subordinate clause is applied and used in the sentence on every news item written on Weverse magazine.